Praxis as a Perspective on International Politics - Hellmann, Gunther; Steffek, Jens.; Project Muse. (Bristol : Bristol University Press, 2022)
Bringing together leading figures in the study of international relations, this collection explores praxis as a perspective on international politics and law. It builds on the transdisciplinary work of Friedrich Kratochwil to reveal the scope, limits and blind spots of praxis theorizing.
9 I Think, Therefore IR? Psychology, Biology and the Notion of Praxis -- Introduction -- The psychology of feelings, cognition and behaviour -- Evolutionary legacy -- From culture to cognition -- Behavioural genetics -- Cultural epigenetics? -- Practising praxis -- Psychobiology of praxis -- Conclusion -- References -- 10 Practice, Intersubjectivity and the Problem of Contingency -- Introduction -- On the problem of cooperation in game theory and beyond -- Contingency and the logic of social facts -- A Humean approach to uncertainty? Institutions as discovery process -- Conclusion -- References
11 The Praxis of Change and Theory.
Description based upon print version of record.
Description based on print version record.
Keywords: international relations; Politique mondiale; Relations internationales; International law; World politics; International relations; Electronic books